Not a pretty picture - Griffith, Tom (<<The>> Criterion Collection, 2024)
"Trailblazing filmmaker Martha Coolidge made her feature debut with this unflinchingly personal hybrid of documentary and fiction. Centered on an intense reenactment of Coolidge’s experience of rape in her adolescence, the film casts Michele Manenti (also a survivor) as the director’s younger self, and observes the actor and her castmates as they engage in a profound dialogue about what it means to recreate these traumatic memories, and about their attitudes concerning consent and self-blame. A high-stakes experiment in metacinema that broke new ground with its uncompromising examination of date rape, Not a Pretty Picture brings a stunning immediacy to questions about the on-screen representation of sexual violence and the limits of artistic catharsis." [criterion.com]
Original: USA 1976
Director-approved DVD special edition features: new 4K digital restoration, supervised and approved by director Martha Coolidge ; interview with Coolidge conducted by filmmaker Allison Anders ; 'Old-fashioned woman' (1974), a documentary by Coolidge about her grandmother ; English subtitles for the deaf and hard of hearing ; plus: an essay by film critic Molly Haskell
Bildformat 1.33:1
Keywords: Vergewaltigung; Mädchen; Film; DVD-Video